2020
DOI: 10.1002/adma.201906939
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermoconductive, Thermostable, and Super‐Flexible Film by Engineering 1D Rigid Rod‐Like Aramid Nanofiber/2D Boron Nitride Nanosheets

Abstract: Polymer‐based thermal management materials have many irreplaceable advantages not found in metals or ceramics, such as easy processing, low density, and excellent flexibility. However, their limited thermal conductivity and unsatisfactory resistance to elevated temperatures (<200 °C) still prevent effective heat dissipation during applications with high‐temperature conditions or powerful operation. Therefore, herein highly thermoconductive and thermostable polymer nanocomposite films prepared by engineering 1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
179
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 289 publications
(185 citation statements)
references
References 51 publications
1
179
1
Order By: Relevance
“…The characteristic peaks of BNNS at 1287 cm −1 assigned to B−N stretching and 750 cm −1 assigned to out‐of‐plane B−N−B bending, exhibited a decreased intensity and shift to 1355 and 765 cm −1 , respectively, with the PU additive. [ 36,40,41 ] Moreover, the randomly distributed BNNSs became highly aligned (bottom inset in Figure 2a) after drawing in the electric field during electrospinning. Note that the drawing‐induced thinning of the PU/BNNS fibers was affected by the phase separation of polymer solutions, which was mainly controlled by the modification of the tri‐solvent system and solid content in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic peaks of BNNS at 1287 cm −1 assigned to B−N stretching and 750 cm −1 assigned to out‐of‐plane B−N−B bending, exhibited a decreased intensity and shift to 1355 and 765 cm −1 , respectively, with the PU additive. [ 36,40,41 ] Moreover, the randomly distributed BNNSs became highly aligned (bottom inset in Figure 2a) after drawing in the electric field during electrospinning. Note that the drawing‐induced thinning of the PU/BNNS fibers was affected by the phase separation of polymer solutions, which was mainly controlled by the modification of the tri‐solvent system and solid content in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, strong interfacial interactions were formed between the elastic PU polymer and the highly aligned BNNS during electrospinning (top inset in Figure 2a), which facilitated the efficient heat flux through the fibrous membranes. [35,36] The crystal structure demonstrated that the PU polymer chain and the (B-N) 3 hexatomic rings were coupled together by hydrogen bonds NH•••N with distances of 2.57 and 2.85 Å. This interfacial interaction can be explained by the electrostatic potential (ESP) analysis, which is a favorable tool to gain information about the reactivity, charge distribution, and hydrogen bonding interaction (detailed in the Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal management plays an increasingly important role in modern technologies, most notably electronics [ 1 , 2 , 3 ] and energy devices. [ 4 , 5 , 6 , 7 ] The ease of processing and electrical insulation properties of organic polymers has made them indispensable for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the primary reason for restricting its use in the field of heat dissipation is that polymers generally have a low thermal conductivity (0.2–0.5 W m −1 K −1 ) [ 3 , 4 ]. Therefore, a variety of thermally conductive fillers, such as graphene, hexagonal boron nitride (h-BN), aluminum nitride, aluminum oxide, and silicon carbide are usually used to improve the thermal conductivity of polymer composites and solve the problem of heat dissipation [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%